Key shifts in frontoparietal network activity in Parkinson’s disease - Ronen Sosnik; Firas Fahoum; Zoya Katzir; Anat Mirelman; Inbal Maidan (npj Parkinson's Disease)
Abstract We aimed to study the effect of Parkinson’s disease (PD) and motor-cognitive load on the interplay between activation level and spatial complexity. To that end, 68 PD patients and 30 controls underwent electroencephalography (EEG) recording while executing visual single- and dual- Go/No-go tasks. The EEG underwent source localization, followed by parcellation of the neural activity into 116 regions of interest. We observed alterations in activity within a distributed network of brain areas associated with attention and inhibition operations, including a circuit pathway connecting frontal and temporal/parietal regions and the limbic network. The alterations in activity were associated with task complexity (single- or dual- task) and group (PD or controls) and encompassed spatial, temporal and spectral dimensions. These results elucidate electrophysiological alterations in four core aspects of brain activity associated with motor-cognitive function in PD patients and hold potential implications for future studies involving adaptive electrical interventions.